2021
DOI: 10.2147/vmrr.s305198
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bovine Viral Diarrhea Virus in Local Borana Cattle Breed and Camels (Camelus dromedarius) in Ethiopia

Abstract: Background: Bovine viral diarrhea, caused by bovine viral diarrhea virus (BVDV), has been considered a disease of cattle but is now emerging in camels. In Ethiopia it has been detected in exotic and cross-bred dairy cattle but no information is available on its occurrence in indigenous cattle breeds and camels. This study was, therefore, conducted to estimate the prevalence of BVDV infection in indigenous Borana cattle and camels (Camelus dromedarius) in Moyale and Miesso pastoral districts. Methodology: Serol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…When compared to camels raised alone and in large herds, the prevalence of BVDV infection was considerably greater in camels in small herds that raised together with small ruminants. A similar results were reached by Ataseven et al [31] and Tesfaye et al [17]. A number of previous studies have been reported that aggregation with other ruminants in pasture, size of herd, age of animals, and introduction of new animals from uncontrolled markets without efficient examination increased the possibility and chance for transmission of many of viral diseases [44][45][46].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…When compared to camels raised alone and in large herds, the prevalence of BVDV infection was considerably greater in camels in small herds that raised together with small ruminants. A similar results were reached by Ataseven et al [31] and Tesfaye et al [17]. A number of previous studies have been reported that aggregation with other ruminants in pasture, size of herd, age of animals, and introduction of new animals from uncontrolled markets without efficient examination increased the possibility and chance for transmission of many of viral diseases [44][45][46].…”
Section: Discussionsupporting
confidence: 76%
“…Commercial ELISA kits (IDvet, Innovative Diagnostics, Grabels, France) for detection of BVDV p80 antibody in serum of examined camels was used, following the manufacturer's instructions. This kit has 100% sensitivity and specificity to identify the presence of circulating antibodies in the serum [17]. The absorbance of the sample was measured at 450 nm using ELISA microplate reader.…”
Section: Sample Size and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The high seroprevalences of BVDV Ab and Ag reported in the preceding primary study by Van Leeuwen et al . [ 26 ] approached or exceeded those of other reports [ 41 , 42 ]. Having a third of tested cattle testing positive for BVDV Ags [ 26 ] was surprising, suggesting that a substantial proportion of cattle had either transient or persistent infections of BVDV at the time of blood sampling, despite showing little or no clinical signs of BVDV disease.…”
Section: Discussionmentioning
confidence: 52%
“…BVDV can cause a wide range of clinical syndromes, including respiratory disease, reproductive dysfunction, immunosuppression, persistent infection, and mucosal diseases [19]. It mainly infects cloven hoofed mammals, such as cattle, camels, deer, sheep, goats, pigs, and so on [20][21][22]. Cattle are typical of BVDV hosts the virus is not restricted to this host.…”
Section: Discussionmentioning
confidence: 99%